2021
DOI: 10.1371/journal.pone.0246010
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of floating toe and its relationship with static postural stability in children: The Yamanashi adjunct study of the Japan Environment and Children’s Study (JECS-Y)

Abstract: Floating toe (FT) is a frequently seen condition in which a toe is inadequately in contact with the ground. Although toes play an important role in stabilizing standing posture and walking, many aspects of the effects of FT on the body remain unclear. To our knowledge, there have been no reports about the relationship between FT and postural stability, especially in children. This study aimed to clarify the prevalence of FT and its relationship with static postural stability in children. Of the 400 children ag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…Tasaka et al examined FT in children aged 9–11 years and reported that the frequency of cases without the toe contacting the ground was 40.3% 7 ) . Fujimaki et al, in their study of 396 cases of 8-year-old children, reported that 97.7% of female and 95.6% of male individuals had FT 9 ) . FT in children is highly prevalent; however, the frequency varies widely.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Tasaka et al examined FT in children aged 9–11 years and reported that the frequency of cases without the toe contacting the ground was 40.3% 7 ) . Fujimaki et al, in their study of 396 cases of 8-year-old children, reported that 97.7% of female and 95.6% of male individuals had FT 9 ) . FT in children is highly prevalent; however, the frequency varies widely.…”
Section: Discussionmentioning
confidence: 98%
“…FT was assessed using a foot pressure plate (Win-Pod, Medicapteurs, Balma, France). The method of measuring FT was the same as mentioned previously 9 ) . The following is a summary of the method.…”
Section: Participants and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Empuja con todo el pie el suelo, y sobre todo con el dedo gordo. así contribuir a la mejora propioceptiva (presión, equilibrio y estabilidad) desde el pie, y poder mejorar su estabilidad en cada movimiento (Fujimaki et al, 2021).…”
Section: ¿Cómo Desarrollar Y Optimizar La Postura En Dinámico?unclassified